Genomic evolution in Barrett’s adenocarcinoma cells: critical roles of elevated hsRAD51, homologous recombination and Alu sequences in the genome - Pal, J (2011)
A prominent feature of most cancers including Barrett’s adenocarcinoma (BAC) is genetic instability, which is associated with development and progression of disease. In this study, we investigated the role of recombinase (hsRAD51), a key component of homologous recombination (HR)/repair, in evolving genomic changes and growth of BAC cells. We show that the expression of RAD51 is elevated in BAC cell lines and tissue specimens, relative to normal cells. HR activity is also elevated and significantly correlates with RAD51 expression in BAC cells. The suppression of RAD51 expression, by short hairpin RNA (shRNA) specifically targeting this gene, significantly prevented BAC cells from acquiring genomic changes to either copy number or heterozygosity (P<0.02) in several independent experiments employing single-nucleotide polymorphism arrays. The reduction in copy-number changes, following shRNA treatment, was confirmed by Comparative Genome Hybridization analyses of the same DNA samples. Moreover, the chromosomal distributions of mutations correlated strongly with frequencies and locations of Alu interspersed repetitive elements on individual chromosomes. We conclude that the hsRAD51 protein level is systematically elevated in BAC, contributes significantly to genomic evolution during serial propagation of these cells and correlates with disease progression. Alu sequences may serve as substrates for elevated HR during cell proliferation in vitro, as they have been reported to do during the evolution of species, and thus may provide additional targets for prevention or treatment of this disease.